Effect of oil prices to the emerging stock market in East Asia and Pacific countries (Malaysia, Indonesia, Philippine and Korea) / Nur Fadilah Ibrahim - Ibrahim, Nur Fadilah (2010)
This study tries to investigate the effect of oil prices to the emerging stock market in East Asia and Pacific countries. The weekly data of oil and stock markets price index of Malaysia, Indonesia, Philippine and Korea for five years running from 7th January 2005 until 25th December 2009 are collected and an Autoregression Model are used in this investigation. The results from models reveal that there is a significant effect of oil price to the emerging stock market. However, the relationships are differing from country to country. Malaysian and Korean stock market are positively affected while Indonesian and Philippine stock market react negatively to oil price fluctuations. The results in this paper are useful for market participants, investors, professional portfolio managers, government agencies and financial literature who are concerned with effect of oil price in emerging stock markets.